SISTEM INFORMASI KEANGGOTAAN PERGERAKAN MAHASISWA ISLAM INDONESIA (PMII) KABUPATEN BANJAR - Fathul Hafidh; Mirza Yogy Kurniawan; Rezky Izzatul Yazidah Anwar (Universitas Palangka Raya, 2021)
The Indonesian Islamic Student Movement (PMII) Banjar Regency is a forum for association of student organizations within the Banjar Regency. The registration process for organizational members is carried out conventionally, which must come to the PMII Kabupaten Banjar then filled out all available forms and collected them back to the administration department. Then a written test is held which will be held on the specified day, after the participant is declared to have passed, then the participant will be invited to carry out an interview test. Documentation of activities on books and paper causes data recording to take a long time due to different handwriting and difficulty in reading them, books and paper are also prone to damage and loss. It is very difficult to find data from previous registered member because there is no good documentation. There is also no standard committee election fee, which creates difficulties in choosing a new committee. With the Information System, the registration service process, written tests until interviews can be well documented and stored, data retrieval becomes faster also data management is more structured. The management system for each member also facilitates the management of existing members in the PMII Kabupaten Banjar and can be used as a reference when forming a committee. Testing User Acceptance on the application of the system gets Cronbach Alpha value of 0.654, which means that the reliability is included.